2017
DOI: 10.1002/etc.3728
|View full text |Cite
|
Sign up to set email alerts
|

The characterization of dissolved organic matter extracted from different sources and their influence on cadmium uptake by Microcystis aeruginosa

Abstract: The present study examines the uptake of the heavy metal cadmium (Cd) by Microcystis aeruginosa in the presence of dissolved organic matter (DOM) from different origins. The DOM used in the present study were extracted from soil, sediment taken from Meiliang Bay at Taihu Lake, and from M. aeruginosa cultured in the laboratory. The 3 different DOM samples were characterized using ultraviolet-visible absorption spectroscopy and Fourier transform infrared spectroscopy. The excitation-emission matrix (EEM) fluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Under this scenario, substantial DOM would be produced and released into soil solutions, and thus was involved in the Fe­(III) co-precipitation to form OFC. Besides, previous studies indicated that DOM from different sources may have different structures and functional groups, which are expected to affect the interactions with Fe­(III) or Cr­(III). In this work, to simulate these conditions, different DOM solutions were extracted from rice and rape straws (DOM_ri; DOM_ra, respectively), and these DOM solutions were used to synthesize OFC through co-precipitation with Fe 3+ . Batch experiments were conducted to investigate the effects of Cr­(III) concentration, pH, and ionic strength on the Cr­(III) sorption to OFC.…”
Section: Introductionmentioning
confidence: 99%
“…Under this scenario, substantial DOM would be produced and released into soil solutions, and thus was involved in the Fe­(III) co-precipitation to form OFC. Besides, previous studies indicated that DOM from different sources may have different structures and functional groups, which are expected to affect the interactions with Fe­(III) or Cr­(III). In this work, to simulate these conditions, different DOM solutions were extracted from rice and rape straws (DOM_ri; DOM_ra, respectively), and these DOM solutions were used to synthesize OFC through co-precipitation with Fe 3+ . Batch experiments were conducted to investigate the effects of Cr­(III) concentration, pH, and ionic strength on the Cr­(III) sorption to OFC.…”
Section: Introductionmentioning
confidence: 99%
“…The absorption spectra of DOM were measured by UV-visible spectrophotometer scanned with a 10 mm quartz cuvette in the wavelength range of 200-700 nm with an interval of 2 nm. The absorption coe cients were calculated based on the equation a(λ) = 2.303×A/l and SUVA λ =a(λ)/DOC, using the absorbance values at 250 nm, 254 nm, 260 nm, 280 nm and 365 nm as A, respectivel (Ni et al 2017).…”
Section: Determination Of Uv-visible Spectral Characteristic Parametersmentioning
confidence: 99%
“…The accumulation of Zn 2+ or Cd 2+ by M. aeruginosa increased exponentially with the initial concentration of metal ions. Ni et al [ 16 ] studied the absorption of cadmium by M. aeruginosa in the presence of dissolved organic matter (DOM) from different sources. It was found that the molecular weight of DOM in sediments and soil in Meiliang Bay of Taihu Lake was lower than that of M. aeruginosa .…”
Section: Introductionmentioning
confidence: 99%